2009
DOI: 10.1007/s12024-009-9105-9
|View full text |Cite
|
Sign up to set email alerts
|

Children, adolescents and young adults suicide data from Epirus, northwestern Greece

Abstract: The aim of this study was to evaluate suicide trends among individuals < or = 24 years of age in the region of Epirus, northwestern Greece, from January 1998 to December 2008. Twenty-one cases were classified as suicides out of 242 total deaths (8.7%). The male to female suicide ratio was 4.25 (17 males and 4 females). The preferred suicide method for those aged > or = 19 years involved firearms, and for those aged < 19 years was hanging. Alcohol was implicated in more than 50% of the suicides and was consumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Moreover, due to the increase of life expectancy and a greater accessibility to health services, the population seem to grow older showing a higher number of old adults, implying a rise in the rates of this group and making them more noticeable than the ones of the young people (Beautrais, Collings, Ehrhardt, & Henare, 2005). Despite the fact that some studies have shown more ideation, planning, and attempts among young people -especially the latter (e.g., Nkansah-Amankra, 2013; ten Have et al, 2013) -, other studies find higher rates of suicide in these people (e.g., Cano et al, 2012;Vougiouklakis, Tsiligianni, & Boumba, 2009). It seems that suicide ideation and attempts tend to appear in young adults, increasing the risk of suicide after puberty (Beautrais et al, 2005;Gisle & Van Hoye, 2013;Ministerio de Sanidad, Política Social e Igualdad, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, due to the increase of life expectancy and a greater accessibility to health services, the population seem to grow older showing a higher number of old adults, implying a rise in the rates of this group and making them more noticeable than the ones of the young people (Beautrais, Collings, Ehrhardt, & Henare, 2005). Despite the fact that some studies have shown more ideation, planning, and attempts among young people -especially the latter (e.g., Nkansah-Amankra, 2013; ten Have et al, 2013) -, other studies find higher rates of suicide in these people (e.g., Cano et al, 2012;Vougiouklakis, Tsiligianni, & Boumba, 2009). It seems that suicide ideation and attempts tend to appear in young adults, increasing the risk of suicide after puberty (Beautrais et al, 2005;Gisle & Van Hoye, 2013;Ministerio de Sanidad, Política Social e Igualdad, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The suicide related to the marital status can be associated with age: although different studies show different rates, most of them are common in people of older age (e.g., Beghi, Rosenbaum, Cerri, & Cornaggia, 2013; Coope et al, 2014). In this group of people is more common to be a widower, and also other risk factors, such as chronical diseases (Fairweather-Schmidt, Anstey, Salim, & Rodgers, 2010), appear and they have a higher intentionality using methods which are more lethal (Ministerio de Sanidad, Política Social e Thomas and Gunnell (2010) 1861-2007 Age = ≥15 Thompson, Dewa, and Phare (2012) 2009 N = 1,817; Age = 18-80 Torresani, Toffol, Scocco, and Fanolla (2014) 2000-2009 N = 525; Age = 0 ≥ 85 Uggla and Mace (2015) 2001 N = 927,134; Age = 16-59 Vougiouklakis, Tsiligianni, and Boumba (2009) 1998-2004Age = 10-24 Note. Data in alphabetical order by author/s.…”
Section: Discussionmentioning
confidence: 99%
“…3 Differences in methods may also be influenced by the age range, sex distribution and ethnic composition of a community. 1,4,5 Suicide in South Australia most often involves hanging, carbon monoxide poisoning, drug overdose, and gunshot wounds. Multiple methods of self-destruction may also be used, but are generally less common.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines children as those aged less than 10 years and adolescents as those aged between 10 and 18 years, respectively (Vougiouklakis et al, 2009). The prevalence of suicide in this age group has been determined to be two or three times higher than the overall prevalence (Arslan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%